Z Wielkopolski na Helikon. Rozważania o życiu i twórczości Bonawentury Czesława Graszyńskiego (1859–1922) w stulecie śmierci polsko-greckiego poety - Witczak, Krzysztof Tomasz (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2022)
The aim of my paper is to present the life and poetical works of Bonawentura Czesław Graszyński (1859–1922), a Polish classical philologist, who wrote a number of tragedies and lyrical poems in Ancient Greek. He was born in Murowana Goślina (Greater Poland). After graduating from the high school in Leszno (Greater Poland), he studied medicine and classical philology from 1879 to 1887 at the University of Greifswald. In 1908 he received awards from the Academy of Athens, as well as George I of Greece. It can be said that Graszyński conquered Mount Helicon as a symbol of poetical mastery in Polish-Greek literature.